Contemporary methods of evaluation of economic performances of hotel and spa operators within the framework of international trade - Kondrashov, Alexey (2014)
The PhD thesis provides a complex analysis of the macroeconomic aspect of tourism and builds new insights in measurement of hotel performances analyzing both the uniform hotels indicators and financial ratios in their relationships to the revenue generation. The thesis results show that tourism due to its effects on net export and investments of EU member states is becoming an important factor contributing to macroeconomic stability. At the same time, the importance of international tourism for EU countries varies depending on its share in country's total exports. Analysis of the balance of payments and the evaluation of the role of tourism provide relevant conclusions that tourism is an important category of international trade in EU countries. Statistical evaluation of hotel operating indicators provided in this research enables to contribute to current theories of "revenue management", which deals with maximizing sales through optimization of hotel indicators. The financial analysis performed on a sample of the largest spa operating companies in the Czech Republic has fulfilled the objective of the work focused on the selection of optimal set of indicators with the high explanatory power of financial performance and condition of the companies examined. This PhD thesis provides new insights and comprehensively examines tourism in macroeconomic and financial perspectives. Therefore it ensures compliance with the requirements of modern post-disciplinary methodological approaches that require exploration of complex phenomena such as tourism using complex approaches.